Determinants Of Modern Contraceptive Use Among Market Women Of The Ashaiman Market In The Greater Accra Region, Ghana - Asiedu, A. (University of Ghana, 2017)
Background: The use of modern contraceptive methods still remains low in sub-Saharan Africa despite the enormous benefits that could be derived from their use. Modern contraceptive use has played a key role in reducing the world’s total fertility rate, especially in developing countries, including Ghana. However, few empirical studies have been done in the Ashaiman Municipal Area of Ghana- a place where fertility rate is high-to identify the factors influencing the uptake of modern contraceptives. This study therefore aimed to identifying the determinants of modern contraceptive use among market women in the Ashaiman municipality. Methods: The study employed a cross sectional design. A structured questionnaire was used in gathering data from a total of 290 market women of reproductive age (18-49 years) just for the purpose of study in the Ashaiman market. Descriptive, bivariate and logistic regression analysis techniques were used to analyze the data. Results: The study found that there was a universal awareness of modern contraceptives among the respondents. However the use of contraceptive was relatively low (37%). Socio-demographic factors such as the age and educational status of women were not significantly associated with use of modern contraceptives. A significant proportion (68.4%) of women who thought using modern contraceptives was bad were not using modern contraceptive (p<0.020). Fear of the side effects (p<0.021), the cost of the service (p<0.030) were also found to be associated with the use of modern contraceptive among the market women. Conclusions: Based on these findings, the study recommends educational programmes to address real and perceived side effects, as well as to ensure that women know what to expect when using modern contraceptive methods.
Thesis (MPH)
Keywords: Modern Contraceptive; Market Women; Ashaiman Market; Greater Accra Region; Ghana